Ácidos graxos não esterificados (NEFAs) e beta-hidroxibutirato (BHBA) na regulação da foliculogênese e epigenética das células endometriais - Ferst, Juliana Germano (2020)
Dairy cows milk production has increased over the past decades as a result of intense genetic selection. However, the advances in genetic selection of dairy herds did not come with an improvement of reproductive parameters. Negative energy balance (NEB) during postpartum period is important risk factor in the establishment of reproductive failure in high producing dairy cows. During NEB, nonesterified fatty acids (NEFAs) and β-hydroxybutyrate (BHBA) levels are increased in the serum and follicular fluid and affect follicular microenvironment and endometrium in cattle. Furthermore, the exact NEFAs and BHBA mechanism of action is not yet established and may occur via nuclear receptors. Therefore, the aim of present study was to investigate NEFAs and BHBA action on folliculogenesis and endometrium, as well as to investigate if peroxisome proliferator activated receptor gamma (PPARG) is involved in their regulation in cattle. In the first study, the aim was to investigate if the PPARG participates in the regulation of dominant follicle development and ovulation. Findings from this study revealed that the relative mRNA abundance of PPARG was similar between dominant and subordinate follicles around follicle deviation, decreased after the LH surge, and increased before ovulation. Intrafollicular injection of Troglitazone (TGZ; a PPARG agonist) inhibited follicular growth and decreased CYP19A1 mRNA abundance in granulosa cells. These findings indicate that PPARG is involved in the regulation of steroidogenesis, follicle growth and ovulation in cattle. In a second study, the aim was to investigate if intrafolicular injection of three most important NEFAs (oleic, stearic and palmitic acids) affects dominant follicle development and mRNA expression of candidate genes in granulosa cells. NEFAs injection reduced follicular growth at 24 and 48 h, demonstrating that the high concentrations of NEFAs are detrimental to follicle development. The mRNA expression of genes related to steroidogenesis energetic metabolism and apoptosis examined were not affected by intrafollicular injection of NEFAs. However, NEFAs affected the follicle growth rate of dominant follicle but the mechanism of action still needs further study. In the final study, we evaluated the effects of NEFAs and BHBA in endometrium cells. Findings from this study showed that in vitro treatment with NEFAs and NEFAs plus BHBA increased lipid accumulation, stimulated reactive oxygen species (ROS), altered the morphology and the mRNA expression of genes related to oxidative stress, apoptosis and glucose transport in the endometrium cells. Also, palmitic acid (PA) was able to modulate the try-methylation of histone 3 lysine 4 (H3K4me3) and the mRNA expression of DNA methyltransferase 1 (DNMT1). Altogether, data present in these studies provided evidence that NEFAs and BHBA are detrimental to follicle development and endometrium cells in cattle.